Ursus arctos Linnaeus 1758 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ursus arctos Linnaeus 1758 Ursus arctos Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 47. Type Locality: "sylvis Europæ frigidæ" restricted by Thomas (1911 a ) to "Northern Sweden.". Vernacular Names: Brown Bear. Subspecies:: Subspecies Ursus arctos subsp. arctos Linnaeus 1758 Subspecies Ursus arctos subsp. alascensis Merriam 1896 Subspecies Ursus arctos subsp. beringianus Middendorff 1851 Subspecies Ursus arctos subsp. californicus Merriam 1896 Subspecies Ursus arctos subsp. collaris F. G. Cuvier 1824 Subspecies Ursus arctos subsp. crowtheri Schinz 1844 Subspecies Ursus arctos subsp. dalli Merriam 1896 Subspecies Ursus arctos subsp. gyas Merriam 1902 Subspecies Ursus arctos subsp. horribilis Ord 1815 Subspecies Ursus arctos subsp. isabellinus Horsfield 1826 Subspecies Ursus arctos subsp. lasiotus Gray 1867 Subspecies Ursus arctos subsp. middendorffi Merriam 1896 Subspecies Ursus arctos subsp. pruinosus Blyth 1854 Subspecies Ursus arctos subsp. sitkensis Merriam 1896 Subspecies Ursus arctos subsp. stikeenensis Merriam 1914 Subspecies Ursus arctos subsp. syriacus Hemprich and Ehrenberg 1828 Distribution: Afghanistan, Albania, Armenia, Austria, Azerbaijan, Belarus, Bhutan, Bosnia and Herzegovina, Bulgaria, N and W China, Croatia, Estonia, Finland, France, Greece, India, Iran, Iraq, Israel, Italy, Japan (Hokkaido), Kazakhstan, Lebanon, Macdeonia, N Mexico, Mongolia, North Korea, Norway, N Pakistan, Poland, Romania, Russia, Serbia and Montenegro, Slovakia, Spain, Sweden, Syria, Turkey, Ukraine, W USA. Conservation: CITES – Appendix I as U. arctos (Mexico, Bhutan, China, and Mongolia populations) and U. a. isabellinus otherwise Appendix II. U. S. ESA – Endangered as U. arctos pruinosus , as U. arctos in Mexico, and as U. a. arctos in Italy. Threatened as U. a. horribilis in the USA (48 conterminous states) except where listed as Experimental Non Essential Populations in portions of Idaho and Montana; IUCN – Extinct as U. a. nelsoni , otherwise Lower Risk (lc). Discussion: Reviewed by Erdbrink (1953), Couturier ...